ITTIHAD DAN MA’RIFAT - Muhammad Asra (IAI Al-Mawaddah Warrahmah Kolaka, 2019)
The relationship of closeness and servitude of Sufis to al-Khaliq gives rise to different perspectives and understandings between Sufis and Sufis. This closeness and closeness underwent elaboration so that it would give birth to two large groups. The first group bases their literary experience on a simple understanding that can be understood by humans at a layman level, and in the second group gives birth to a complex and deep understanding using symbolic philosophical languages. This second understanding gives birth (unity / Ittihad) and has implications for the understanding of humans as God's creatures. For them, humans are perfect beings, emanations and the final form of God's manifestation and at the same time become the starting point to know Him, ma'rifat Allâh. By knowing the human self, God will be known because all His images are encapsulated in the human being himself as a perfect human being, with this perfection there can be an inner or spiritual union with God (Al-Ittihad).